Evaluation of the Academic Information System Quality at Universitas Islam Negeri Raden Fatah Palembang Using the McCall Method - Nabella Syahrani (Jurnal Ilmu Komputer dan Sistem Informasi |JIKSI|, 2024)
The presence of information systems in higher education institutions plays a vital role in improving academic and administrative management. A high-quality information system ensures efficient data processing and supports decision-making processes. However, to ensure optimal performance, a system must undergo a thorough quality evaluation. This study aims to evaluate the quality of the Academic Information System (Sistem Informasi Akademik, SIAKAD) of Universitas Islam Negeri (UIN) Raden Fatah Palembang using the McCall Software Quality Model, which focuses on three key dimensions: product operation, product revision, and product transition. The study employs a quantitative research method involving 100 respondents consisting of students and academic staff. Data were analyzed using SPSS, including validity and reliability testing, as well as descriptive statistical analysis. The findings reveal that the Academic Information System at UIN Raden Fatah Palembang has an overall quality score of 85%, classified as â€œVery Good.â€ The results suggest that the system effectively supports academic processes through reliable functionality and user satisfaction, though minor improvements are required in terms of interface responsiveness and mobile access optimization.